ANALISIS DUPONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT KERETA API INDONESIA (PERSERO) - L. Tobing, Vargo Christian; Simatupang, Eva Malina (Aktiva : Jurnal Akuntansi dan Investasi, 2024)
To understand the financial performance of PT KAI (Persero) and the factors influencing it through financial statement analysis using the DuPont System method. This study uses descriptive research, with secondary data sources collected through documentation of PT KAI (Persero) 's Financial Statements. The results of the analysis show that the Return on Equity (ROE) of PT Kereta Api Indonesia (Persero) fluctuated during the period, with a significant increase in 2019 but a decrease in 2020 due to the COVID-19 pandemic. The DuPont System analysis shows that the decrease in ROE is caused by a decrease in profit margin and asset turnover. Therefore, the company needs to take steps to improve its financial performance, such as increasing operational efficiency, optimizing asset utilization, and diversifying products or services. This research is expected to provide useful input for the management of PT Kereta Api Indonesia (Persero) in making strategic decisions to improve the company's financial performance.